Global energy confinement in the initial limiter configuration of Wendelstein 7-X. (29th August 2018) - Fuchert, G.; Bozhenkov, S.A.; Pablant, N.; Rahbarnia, K.; Turkin, Y.; Alonso, A.; Andreeva, T.; Beidler, C.D.; Beurskens, M.; Dinklage, A.; Geiger, J.; Hirsch, M.; et al.
Abstract: Global confinement properties of the limiter plasmas of the first operational campaign of W7-X are investigated with special focus on the energy confinement and possible operational limits. The energy confinement time was found to be close to expectations from the empirical ISS04 scaling for stellarators. Absolute values up to were achieved. This can be considered as a great success for the initial operation of the device. However, a clear degradation of the performance was observed when radiative losses became significant, which was typically the case at low heating power. While a significant improvement of the plasma purity is expected during divertor operation, the presented results underline the importance of the impurity dynamics for the development of high-performance steady-state scenarios in W7-X. Furthermore, comparisons of the global performance properties with neoclassical transport modeling are presented. These studies are not yet fully conclusive, which could indicate that anomalous transport may have played an essential role in the low-density OP1.1 plasmas.